Perancangan Instrumen Bakat Dan Minat Untuk Siswa Di Jenjang Sekolah Menengah Atas (Prosiding Konseling Kearifan Nusantara (KKN), 2022)
Changes in the independent learning curriculum change the pattern of student interest in schools into the selection of subject groups that are tailored to talents and interests. Changes in specialization are of course carried out by guidance and counseling teachers. Guidance and counseling teachers need to update the instruments used to be more comprehensive in measuring students' interests and talents, while the instruments commonly used by guidance and counseling teachers are interviews, sociometry, and interest aptitude tests in collaboration with psychology institutions. There is a need to develop talent and interest instruments that are more flexible for use in schools and are low-cost. This study aims to develop talent and interest instruments using Microsoft Excel. Microsoft excel was chosen because it is relatively easy to use among teachers. In designing the instrument, there are several menus, one of which is individual results, aspect analysis results, and results diagrams. The benefits of designing this instrument are expected to later be used in schools to assist guidance and counseling teachers in identifying students' talents and interests and directing students to subject groups that suit students' interests and talents